Pemberian Buah Sebagai Upaya Pencegahan Stunting bagi Anak-Anak Desa Kepau Jaya - Pernantah, Piki Setri; Hananti, Amalia Luthfiah; Pratama, Andika Dio; Zulrafli, Arif; Miranty, Melly Atma; Geravayahd, M. Alvis; Mayza, Nada Ardia Fika; Putri, Riski Ameliya; Kirani, Sandra; Ningsih, Sulistiana (Journal of Community Engagement Research for Sustainability, 2022)
Stunting is due to nutrient deficiency during the first thousand days. The problem of stunting in developing countries like Indonesia is one of the children's health problems that must be dealt with seriously and continuously. Because this problem can cause irreversible disturbances to physical development and impaired cognitive capacity in children. In addition, the problem of stunting is also at risk for heart disease, high blood pressure and obesity. The team carried out an application method in the form of giving fruit which aims to prevent stunting for the welfare of children and the local community. From the program of activities that have been carried out, there is a result where a striking change in children when given fruit is that children feel happy and happy and participate enthusiastically in eating fruit which is a program to improve nutritional quality. Feelings of fun and joy among children are a signal that children experience cognitive development. Cognitive development refers to reducing the scale of growth retardation in children. Parents of children were also satisfied with the program and concluded that child development should in fact be considered for the quality of a prosperous nation.